A cluster-based yard template design integrated with yard crane deployment using a placement heuristic. (April 2022) - Wang, Mengyao; Zhou, Chenhao; Wang, Aihu
Abstract: The increasing demand for container transportation calls for higher terminal storage capacity and greater handling efficiency. A good yard template design will facilitate both space and yard crane utilization. However, most of the existing research designs the template based on the parallel layout and caters only to destination vessels. This study proposes a cluster-based yard template design method that reserves storage space based on the container destination and origin, which helps avoid yard crane conflict and is therefore applicable to various yard designs. A mixed integer programming model is proposed to assign clusters considering yard crane deployment, with the objective to ensure the yard space is used intensively most of the time. To solve this problem in large-scale cases, three heuristics are developed based on the best-fit method in solving the bin packing problem. Numerical experiments under different yard layouts are conducted to validate the efficiency and effectiveness of the model and algorithms. Highlights: Yard template is designed for transshipment and export cargo in different layouts. Continuous stretch bays are reserved and shared among several container batches. This work allows flexible cargo storage under capacitated yard crane throughput. The proposed problem can be converted into the bin packing problem. Three placement-heuristic-based algorithms are evaluated with large-scale cases.